Rancang Bangun Sistem Informasi Pengaduan Konsumen Area Muara Di PT.Telkom Akses Berbasis Web - Yakup, Muhamad Abdul; Sharyanto, Sharyanto; Bani, Alexius Ulan (Journal of Engineering, Technology and Computing (JETCom), 2024)
PT Telkom Akses, a subsidiary of Telkom Indonesia, specializes in the construction of network infrastructure and provides high-quality and affordable internet connectivity. However, the company faces challenges in managing consumer complaints, which are currently handled manually, leading to potential human errors and inefficiencies. This research aims to design and develop a web-based consumer complaint management system to enhance the accuracy and efficiency of the complaint process. The system is developed using PHP for programming and MySQL for the database. To ensure that the system meets user requirements, Unified Modeling Language (UML) techniques are employed, including use case diagrams, activity diagrams, and class diagrams. Black Box Testing is used to validate the system’s functionality and performance. The implementation of this information system is expected to streamline and improve the management of consumer complaints, particularly in the Muara Karang area, making the process more integrated, accurate, and user-friendly, thereby enhancing service quality and customer satisfaction.